A study of deformation twinning in a titanium alloy by X-ray diffraction contrast tomography. (15th February 2016) - Nervo, Laura; King, Andrew; Fitzner, Arnas; Ludwig, Wolfgang; Preuss, Michael
Abstract: A specimen of Ti–4Al deformed in-situ to about 0.7% compressive strain using neutron diffraction, and showing early stages of twinning, has been investigated in 3D using synchrotron X-ray diffraction contrast tomography (DCT). A cylindrical volume of 900 μm × 400 μm diameter was observed using DCT, containing about 400 grains of which almost 60 grains were identified to have twinned predominantly by 10 1 ¯ 2 〈 1 ¯ 011 〉 011 tensile twinning. To consider possible twin nucleation criteria, non-twinned grains of similar orientation to the twinned grains were compared against the family of twinned grains. Such comparison highlights that the twinned grain family has a grain size distribution shifted to a higher mean value than the corresponding family of grains that has not twinned. An initial neighbourhood analysis did not reveal any significant differences of the two grain families. However, complex twin chains and clusters were identified forming a slightly imperfect network demonstrating the importance of the 3D analysis. Analysis of the parent grain orientations within those chains/clusters using the Luster-Morris parameter revealed a significantly higher propensity of prismatic 〈 a 〉 slip transfer compared to the neighbourhood of the non-twinned grain family while no difference was observed for the likelihood of twin shear transfer. The findings suggest that grain chains/clusters with high ability of prismatic 〈 a 〉 slip activity and slip transfer does promote formation and clustering of twins, which is likely associated with the build up of tensile intergranular strain along the 〈 c 〉 axis perpendicular to the loading direction recently suggested by crystal plasticity modelling. Graphical abstract: